The Conception of Cluster Support Policy in the Realities of the Polish Economy - Każmierski, Jan (Managerial Economics, 2012)
Over the years clusters have become a phenomenon of every economy. They should be treated as a vital mechanism that activates region development. Therefore, cluster-based policy gains an exceptional meaning. Selecting that model of policy, the problem of public aid and support instrument`s appliance are crucial issues. Beside the aspects that were mentioned above, the author also discusses barriers and limitations which are connected with cluster-based policy. He also indicates the ways to overcome them. The conclusions and implications that are presented are for the most part the aftermath of the author`s own empirical research on cluster development issues